Pengaruh Lingkungan Kerja, Kepuasan Kerja, Disiplin Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Dinas Kesehatan Kabupaten Labuhanbatu - Vika Fauziah; Yuniman Zebua; Raja Saol Martho Hendry (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This research aims to determine the influence of the work environment, job satisfaction, discipline and workload on the performance of Labuhanbatu District Health Service employees. The sample in this study was 80 employees at the Labuhanbatu District Health Service. The method used in this research is a quantitative descriptive method. The research results stated that the work environment, job satisfaction, discipline and workload influenced the performance of Labuhanbatu District Health Service employees.